IMPLEMENTATION OF THE MINISTER OF TRANSPORTATION REGULATION NUMBER 45 OF 2020 CONCERNING CERTAIN VEHICLES USING ELECTRIC MOTORS (A CASE STUDY OF STUDENTS AS ELECTRIC BICYCLE USERS) IN PARINGIN DISTRICT, BALANGAN REGENCY - Zahratun Azizah; M. Husaini; Djayeng Turano Gunade (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
This study aims to analyze the implementation of the Over Dimension and Over Loading (ODOL) policy on Brigjen H. Hasan Basri Road, Hulu Sungai Utara Regency, and to identify the factors influencing its implementation. This research employs a qualitative approach with a descriptive research design. Data were collected through observation, in-depth interviews, and documentation involving officers of the Transportation Agency, Traffic Unit of the Hulu Sungai Utara Police, freight drivers, and transport business owners. Data analysis was conducted qualitatively using an interactive analysis model and the policy implementation framework of Van Meter and Horn. The results indicate that the implementation of the ODOL policy has been carried out but has not yet operated optimally. This is evidenced by the continued occurrence of violations due to limited resources, ineffective policy communication, and social and economic pressures affecting the compliance of target groups. The study concludes that the successful implementation of the ODOL policy requires strengthening resources, improving inter-agency coordination, and increasing public awareness and compliance to ensure that the policy can be implemented effectively and sustainably.